Hydrochemical Characteristics of Groundwater in Yinchuan Plain and Their Control Factors - Hui, Qian; Peiyue, Li (Asian Journal of Chemistry, 2011)
Based on the geology and hydrogeology, the hydrochemical characteristics of phreatic water and the first confined water in Yinchuan Plain were analyzed according to the chemical analysis results of 364 water samples and 88 soil samples collected in year 2003, using statistical and geostatistical methods. The factors controlling the compositions of groundwater were investigated as well. Results show along the flow direction from SW to NE, the TDS, concentrations of Na+, Cl– of phreatic water generally increase and the chemical types change in the sequences of HCO3– --> HCO3– + SO42- --> SO42- + HCO3– --> SO42- + Cl– --> Cl– + SO42-. TDS in the first confined water shows a zonation characteristic from west to east. The chemical types of confined water show a similar distribution to phreatic water. The factors controlling and affecting the chemical compositions of groundwater in Yinchuan Plain are mainly (1) geological and hydrogeological conditions, (2) the compositions of recharge water, (3) the soluble salt content of soils, (4) water-rock interaction and (5) evaporation of phreatic water.